PENGARUH EFEKTIVITAS KREDIT USAHA RAKYAT (KUR) SYARIAH TERHADAP PENINGKATAN PROFIT USAHA MIKRO NASABAH BANK BSI KCP ISKANDAR MUDA - Annisa Putri Siregar; Zuhrinal M. Nawawi; Tuti Anggraini (Media Ekonomi, 2023)
This research aims for readers to know the impact of Sharia people’s Business Credit (KUR) on the profit growth of BSI Kcp Iskandar Muda micro business. The relationship and influence between variables can be determined through quantitative research methods. 193 categories of customer communities are in arrears on People’s. Business credit (KUR) at Bank BSI Kep Iskandar Muda, with the sample size selected from the Slovin formula. In collecting data in this research, the technique used was a questionnaire to see the impact of Sharia KUR on micro business profits at Bank BSI KCP Iskandar Muda. The SPSS version 23.0 program is a reference in calculating variables. It is used in the data analysis process. Kredit Usaha Rakyat Syariah influences the total profits of Bank BSI KCP Iskandar Muda Micro Businesses. The data taken are the results obtained during the research. This process can be seen through tcount which is greater than ttable. There is a strong ending with the benchmark Ho being rejected and Ha being accepted.